Ramadan and Eid - Khan,Saniyasnain (Goodword book, 2021)
Ramadan and Eid" is a delightful board book designed for young Muslim children. It uses simple language and bright illustrations to explain the essence of Ramadan$1 (Bfasting, prayer, kindness, and thankfulness. It also highlights the joy of Eid, making it a meaningful way to nurture faith and positive values. With its sturdy design, it is perfect for toddlers$1 (Bsmall hands and repeated reading. The book not only teaches Islamic values but also helps create cherished family moments during Ramadan and Eid.s
This board book beautifully introduces toddlers and preschoolers to the values and practices of Ramadan and Eid in a simple and engaging way. It serves as both a faith-based learning tool and a joyful reading experience, helping young children understand patience, kindness, and gratitude while enjoying vibrant illustrations.
Age Group: Toddlers and preschoolers (under 5 years) Primary Audience: Muslim families with young children Secondary Audience: Educators and Islamic schools looking for faith-based teaching resources Occasion: Ramadan and Eid gifts, bedtime reading, and family learning